Earthcomm Model's Influence on Spatial Thinking Capacity and Environmental Care Character Development: A Focused Study - Joice Zhenrike Memmase; Sumarmi Sumarmi; Purwanto Purwanto (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2024)
Geography learning can be conducted with an Earthcomm learning model covering cognitive and affective skills. Solving these environmental challenges requires geographic and environmental literacy. This research evaluates the effectiveness of the Earthcomm model in enhancing spatial thinking and environmental care for high school students in Bululawang. A quasi-experimental design with pre- and post-tests randomly assigned 72 students to experimental and control groups. Instruments used were a 10-question spatial thinking essay, a 30-question environmental care survey, and Earthcomm-based worksheets. Analysis showed significant effects of the educational intervention on spatial thinking (p = 0.000) and environmental care (p = 0.023). Thus, a statistically significant correlation exists between those variables (p= 0,000), indicating that improving spatial skills may lead to greater environmental responsibility. The N Gain Score (NGS) assessment reveals that this model, with 47.9% NGS, is